Intervention with Purple Okra Pudding and Supplement to Improve Antioxidant Status in Healthy Adults - Damayanthi, Evy; Mira Dewi; Muhammad Aries; Nasution, Zuraidah (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This research aimed to analyze the potency of purple okra-based products in improving the antioxidant status of healthy adults. Thirty adults with high body fat percentages were allocated into three groups: the first group was treated with 100 g of purple okra pudding/day, the second group was provided with a purple okra extract supplement that contained 3.80 g of extract/day, and the third group was a control group. The intervention was carried out for 28 days. All subjects were exposed to nutrition education, and data on their characteristics, food intake, and physical activity level were collected. The results showed that purple okra pudding and supplement had antioxidant activity of 0.39 and 455.39 mg AEAC/g extract, IC50 of 543.79 and 71.78 ppm, and total phenol of 6.21 and 24.49 mg GAE/g extract, respectively. There were significant differences among subject groups in energy, protein, and fat intake as well as physical activity level. The group treated with purple okra pudding showed a significantly higher ΔSOD after the intervention, most probably due to the role of antioxidants contained in purple okra in upregulating antioxidant defense. In contrary, there was a declining trend of ΔSOD in the group treated with purple okra extract supplement. The different effects observed between the two groups might be due to the different phenol contents between the two intervention products. This study showed that purple okra has the potential as a functional food and health supplement in improving the antioxidant status of healthy adults with high body fat percentages as indicated by a higher change of SOD level (0.08 u/mL) in comparison to the control (-0.07 u/mL).